Enhancing sensitivity and versatility of Tn5-based single cell omics - Seufert, Isabelle; Sant, Pooja; Bauer, Katharina; Syed, Afzal P.; Rippe, Karsten; Mallm, Jan-Philipp (Frontiers in Epigenetics and Epigenomics, 2023)
The analysis of chromatin features in single cells centers around Tn5 transposase and exploits its activity to simultaneously fragment target DNA and integrate adapter sequences of choice. This reaction provides a direct readout in the assay for transposase-accessible chromatin in single cells (scATAC-seq) to map open chromatin loci. However, a current limitation is the sparse coverage of these open sites in a given single cell by droplet-based methods. Thus, enhancing Tn5 activity to improve genomic coverage of scATAC-seq or facilitating multi-omics readouts of chromatin features via Tn5 together with the transcriptome is of great interest. Here, we address these issues by optimizing scATAC-seq for an increased number of integrations per cell. In addition, we provide a protocol that combines mapping of histone modification with scRNA-seq from the same cell by targeting Tn5 to antibody-bound chromatin epitopes. Our experimental workflows improve the results obtained from the downstream data analysis and serve to better resolve epigenetic heterogeneity and transcription regulation in single cells.